Varina : a novel - Frazier, Charles, 1950- (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2018)
"Her marriage prospects limited, teenage Varina Howell agrees to wed the much-older widower Jefferson Davis, with whom she expects the secure life of a Mississippi landowner. Davis instead pursues a career in politics and is eventually appointed president of the Confederacy, placing Varina at the white-hot center of one of the darkest moments in American history"--
Includes bibliographical references (page 356).
Keywords: Davis, Varina, -- 1826-1906 -- Fiction; Davis, Jefferson, -- 1808-1889 -- Fiction; Davis, Varina, -- 1826-1906; Davis, Jefferson, -- 1808-1889; Davis, Varina, -- 1826-1906 -- Fiction; 1861-1865; Man-woman relationships -- Fiction; FICTION -- Historical -- General; FICTION -- Biographical; FICTION -- War & Military; Man-woman relationships; Man-woman relationship -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; United States; United States -- History -- 1861-1865, Civil War -- Fiction; Historical fiction; Biographical fiction; History; Historical fiction; Fiction; Biographical fiction; Historical fiction; Biographical fiction; Historical fiction; Biographical fiction; Novels; Historical fiction